Regulated Deficit Irrigation (RDI) in fruit crops: best alternative to grow quality fruit with minimum water facility - Sau, Sayan; Bhattacharjee, Panchal; Shankar, Kripa (Indian Horticulture, 2022)
Among several environmental stresses deficient water status is a major concern over the world and impacted a lot on growth of plant thereby ultimately on yield and quality of the produce. This impact of water stress is significant on fruit crops equally as on other crops. But, to ensure food and nutritional security for ever increasing world population, diversified crop production will need to be significantly increased coping with several stress situations as with our present concern the water deficit